2010
DOI: 10.1227/01.neu.0000377859.06219.78
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Perivascular Localization of Mesenchymal Stem Cells From Mouse Brain

Abstract: BACKGROUND Although originally isolated from the bone marrow, mesenchymal stem cells (MSCs) have recently been detected in other tissues. However, little is known about MSCs in the brain. OBJECTIVE To determine the extent to which cells with the features of MSCs exist in normal brain tissue and to determine the location of these cells in the brain. METHODS Single-cell suspensions from mouse brains were cultured according to the same methods used for culturing bone marrow–derived MSCs (BM-MSCs). These brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 49 publications
2
59
0
Order By: Relevance
“…[32][33] MSCs have been subsequently found in many tissues, such as umbilical cord blood, adipose, brain, liver and lungs. [34][35][36][37][38][39][40] They seen as promising cells for the treatment of a large variety of disorders, including cardiovascular, neurodegenerative and autoimmune diseases.…”
Section: -31mentioning
confidence: 99%
“…[32][33] MSCs have been subsequently found in many tissues, such as umbilical cord blood, adipose, brain, liver and lungs. [34][35][36][37][38][39][40] They seen as promising cells for the treatment of a large variety of disorders, including cardiovascular, neurodegenerative and autoimmune diseases.…”
Section: -31mentioning
confidence: 99%
“…The majority of these Sca-1 + cells are ECs (Fig. 1A), a finding common to other organs, such as the liver, lung, and brain [44][45][46][47][48]. Oh et al first reported a population of Sca-1 + cells from murine adult myocardium with telomerase activity analogous to that observed in newborn heart.…”
mentioning
confidence: 91%
“…8 Moreover, PCs of different organs, including the brain, have been reported to possess mesenchymal stem cell characteristics with the potential to differentiate in vitro into bone, cartilage, or adipose tissue. [9][10][11] The plasticity of PCs is underscored by reports, which suggested multipotent stem cell characteristics of CNS microvascular PCs. 12 With the increasing interest in the complex functions of PCs and mural cells, new questions arise as to how PCs may be affected by pathologic conditions of the CNS.…”
Section: Introductionmentioning
confidence: 99%